Not Just Childâ??s Play : Emerging Tradition and the Lost Boys of Sudan - McMahon, Felicia R., 1950- (Book collections on Project MUSE., 2007)
Felicia R. McMahon breaks new ground in the presentation and analysis of emerging traditions of the \"Lost Boys, \" a group of parentless youths who fled Sudan under tragic circumstances in the 1990s. With compelling insight, McMahon analyzes the oral traditions of the DiDinga Lost Boys, about whom very little is known. Her vibrant ethnography provides intriguing details about the performances and conversations of the young DiDinga in Syra-cuse, New York. It also offers important insights to scholars and others who work with refugee groups. The author argues that the playful tradition